PENGARUH CITY BRANDING TERHADAP CITY IMAGE, CUSTOMER SATISFACTION, DAN CUSTOMER LOYALTY DI KOTA AMBON - Salampessy, Haris; Suroso, Imam; Wulandari, Deasy (BISMA: Jurnal Bisnis dan Manajemen, 2015)
Abstract:The purpose ofthis study was to examine the effect of city branding on city image, customer satisfaction, and customer loyalty in Ambon City. The population was the domestic and foreign tourists who visited tourism spots in Ambon. Sampling method used was purposive sampling with a sample size of 160 respondents. The analysis too lused was Stuctural Equation Modelling. Results showed that there was a significant effect of city branding on city Image, city branding on customer satisfaction, city branding on customer loyalty, city image on customer satisfaction, city image on customer loyalty, and customer satisfaction on customer loyalty in Ambon City. Keywords: City Branding, City Image, Customer Satisfaction, Customer Loyalty.